Combining bulk and single-cell RNA-sequencing data to reveal gene expression pattern of chondrocytes in the osteoarthritic knee. Issue 1 (1st January 2021) - Li, Xiaoyu; Liao, Zheting; Deng, Zhonghao; Chen, Nachun; Zhao, Liang
ABSTRACT: Osteoarthritis (OA) occurs mostly in the knees, hips, finger interphalangeal joints, and spinal facet joints, and is characterized by cartilage degeneration. The existing bulk RNA sequencing (bulk RNA-seq) and single-cell sequencing (scRNA-seq) data for chondrocytes in the osteoarthritic knee joint provide the expression profiles of entire cell populations and individual cells, respectively. Here, we aimed to analyze these two types of sequencing data in order to obtain a more comprehensive understanding of OA. We compared the analysis results of bulk RNA-seq and scRNA-seq from the dataset GSE114007 and the dataset GSE104782, respectively, and identified the differentially expressed genes (DEGs). Then, we tried to find the key The transcription factor is a more fomal term (TFs) and long non-coding RNA (lncRNA) regulation. We highlighted 271 genes that were simultaneously suggested by these two types of data and provided their possible expression pattern in OA. Among the 271 genes, we identified 14 TFs, and TWIST2, MYBL2, RELA, JUN, KLF4, and PTTG1 could be the key TFs for the 271 genes. We also found that 8 lncRNAs among the 271 genes and the lncRNA regulation between CYTOR and NRP1 could contribute to the pain and vascularization of cartilage in the osteoarthritic knee. In short, our research combined the analysis results of bulk RNA-seq and scRNA-seq data for OA chondrocytes, which will contribute to further elucidation of the molecular mechanisms of OA pathogenesis. uf0001